2021
DOI: 10.1021/acsaem.0c02834
|View full text |Cite
|
Sign up to set email alerts
|

Cowpea-like N-Doped Silicon Oxycarbide/Carbon Nanofibers as Anodes for High-Performance Lithium-Ion Batteries

Abstract: Silicon oxycarbide (SiOC) is considered as a potential anode material in lithium-ion batteries because of its high theoretical capacity and good structural stability. Despite many such assets, its low electronic conductivity causes poor rate capability and rapid attenuation of capacity. Herein, we report the fabrication of cowpea-like N-doped carbon nanofiber-encapsulated SiOC spheres (SiOC/C NFs) in which the Si−N bridging is introduced into SiOC. Our method not only demonstrates an improved electronic conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…By forming a percolation network, carbonaceous materials boost the electrical conductivity of the system as well as enhance Li storage capacity and electron transfer kinetics. Numerous studies have focused on the incorporation of carbon materials into the SiOC material system, including carbon nanotubes, , graphite, graphene nanoplatelets (GNPs), graphene oxide, , reduced graphene oxide, and carbon nanofibers. , Various processing methods have been employed to develop 2D carbonaceous-based SiOC anodes, like ball milling, physical mixing, sol–gel infiltration, precursor infiltration, in situ reaction, and electrospinning. , ,, …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…By forming a percolation network, carbonaceous materials boost the electrical conductivity of the system as well as enhance Li storage capacity and electron transfer kinetics. Numerous studies have focused on the incorporation of carbon materials into the SiOC material system, including carbon nanotubes, , graphite, graphene nanoplatelets (GNPs), graphene oxide, , reduced graphene oxide, and carbon nanofibers. , Various processing methods have been employed to develop 2D carbonaceous-based SiOC anodes, like ball milling, physical mixing, sol–gel infiltration, precursor infiltration, in situ reaction, and electrospinning. , ,, …”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have focused on the incorporation of carbon materials into the SiOC material system, including carbon nanotubes, 27,28 graphite, 29−32 graphene nanoplatelets (GNPs), 33−38 graphene oxide, 39,40 reduced graphene oxide, 41−43 and carbon nanofibers. 44,45 Various processing methods have been employed to develop 2D carbonaceous-based SiOC anodes, like ball milling, physical mixing, sol−gel infiltration, precursor infiltration, in situ reaction, and electrospinning. 27,[34][35][36][37]43,45 However, a few recent reports on current collectors suggested that the surface roughness, structure, wettability, flexibility, compressibility, safety, and weight of the collector are important factors that need to be considered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ordinarily, the electrode materials determine the electrochemical performance of LIBs, e.g., energy and power density, cycling lifetime, etc . Therefore, current studies are mainly focused on developing advanced anode materials that possess fast ion transportation dynamics and robust structure to replace the widely used commercial graphite anodes and satisfy the current market demand. Nowadays, based on different Li-storage mechanisms, most anode materials can be classified into three types: insertion-type anodes (hard carbon, graphite), alloy-type anodes (Sn, Bi, Sb), and conversion-type anodes (WS 2 , MoS 2 , VN). , Typically, compared with the others, conversion reactions are able to avoid huge volume swelling and manifest large theoretical specific capacity (ranging from 500 to 1000 mA h g –1 ). , …”
Section: Introductionmentioning
confidence: 99%
“…5−7 Nowadays, based on different Li-storage mechanisms, most anode materials can be classified into three types: insertiontype anodes (hard carbon, graphite), alloy-type anodes (Sn, Bi, Sb), and conversion-type anodes (WS 2 , MoS 2 , VN). 8,9 Typically, compared with the others, conversion reactions are able to avoid huge volume swelling and manifest large theoretical specific capacity (ranging from 500 to 1000 mA h g −1 ). 10,11 Among these conversion-type anode materials, transitionmetal sulfides (TMDs) have attracted widespread attention in terms of energy storage due to their unique graphite-like layered structure and special physical and chemical properties.…”
Section: Introductionmentioning
confidence: 99%